Radiological Risk Assessment and Radioactivity Concentration in sediment of Tigris River of the Medical City/Bab Al Muadham - Jameel, Athraa Naji (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The concentrations of natural radionuclides in sediment samples from various locations along the stream of the Tigris riverbank in the Medical city in Bab Al- Muadham, Baghdad, had been examined using NaI(Tl) detector. The mean concentrations of specific activity for 238U, 232Th, 40K and 137Cs for sediments of the river was 13.5±4.6, 35.2±3.1, 272.2±21.4 and 1.5±0.35 Bq/kg respectively. The findings revealed that the concentration values of natural radionuclides and cesium were below permitted limits. The radiological hazard was compared with a global average (Radium equivalent, absorbed dose rate, radiation hazard index and annual effective dose equivalent) finding it was less than reported by UNSCEAR . The radium equivalent activity was 102.22 Bq/kg and the maximum absorbed dose rate was 88.1 nGy/h. At the same time, the mean annual effective dose equivalent was 420.1 µSv/y. The highest risk index was 0.39 and is much less than 1, except for the lifetime cancer risk were valuing between 164.2×10−3 to 1620×10 −3. This is a higher value than the global average.